2009
DOI: 10.3354/meps07725
|View full text |Cite
|
Sign up to set email alerts
|

Deep into the ice: over-wintering and habitat selection in male Atlantic walruses

Abstract: New technological developments in animal-borne satellite-tracking devices in combination with increased access to satellite-based environmental data are creating new possibilities for studying movement patterns and habitat selection by animals in remote, logistically challenging environments. In the present study, we report the first year-round data on movement patterns of walruses in the High Arctic, including at-sea positions. Using first-passage times (FPT) to study habitat use and quantifying habitat selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…In the winter, walrus distribution appears to be largely independent of ice cover and ice movement (Born et al 2005, Freitas et al 2009, Jay et al 2010. In summer, the variability in the numbers and proportions of the population at haulouts is high within and between years (Table 7) and there may be different drivers guiding haulout patterns for different age and sex classes.…”
Section: Survey Designmentioning
confidence: 99%
“…In the winter, walrus distribution appears to be largely independent of ice cover and ice movement (Born et al 2005, Freitas et al 2009, Jay et al 2010. In summer, the variability in the numbers and proportions of the population at haulouts is high within and between years (Table 7) and there may be different drivers guiding haulout patterns for different age and sex classes.…”
Section: Survey Designmentioning
confidence: 99%
“…Hidden Markov model [58,59], first passage time [60], state space model [61,62]) and used to relate the defined horizontal ARS to particular structures of the environment (e.g. oceanographic features [31,53,63], sea ice [64,65], topography [66,67]). Bailleul et al [36] underlined the importance of integrating a vertical index of foraging effort to better identify foraging areas when studying deep-diving marine predators.…”
Section: Ecological Applicationsmentioning
confidence: 99%
“…We therefore suggest that Freitas et al (2009) have identified the breeding areas for these males during these two breeding seasons.…”
Section: Fig 4 Maximum Depth Of the Dives Recorded From Four Of The mentioning
confidence: 93%
“…The tag design was therefore adjusted prior to the 2003 summer season to include a protective ridge in front of the antennae (Fig. 2), which greatly improved the longevity of the tags Freitas et al 2009). …”
Section: Satellite Telemetrymentioning
confidence: 99%
See 1 more Smart Citation